Depression treatment and healthcare expenditures among elderly Medicare beneficiaries with newly diagnosed depression and incident breast, colorectal, or prostate cancer - Alwhaibi, Monira (Psychooncology, 2017)
OBJECTIVES: Depression is associated with high healthcare expenditures, and depression treatment may reduce healthcare expenditures. However, to date, there have not been any studies on the effect of depression treatment on healthcare expenditures among cancer survivors. Therefore, this study examined the association between depression treatment and healthcare expenditures among elderly with depression and incident cancer. METHODS: The current study used a retrospective longitudinal study design, the linked Surveillance, Epidemiology, and End Results–Medicare database. Elderly (≥66 years) fee-for-service Medicare beneficiaries with newly diagnosed depression and incident breast, colorectal, or prostate cancer (N = 1502) were followed for a period of 12 months after depression diagnosis. Healthcare expenditures were measured every month for a period of 12-month follow-up period. Depression treatment was identified during the 6-month follow-up period. The adjusted associations between depression treatment and healthcare expenditures were analyzed with generalized linear mixed model regressions with gamma distribution and log link after controlling for other factors. RESULTS: The average 1-year total healthcare expenditures after depression diagnosis were $38 219 for those who did not receive depression treatment; $42 090 for those treated with antidepressants only; $46 913 for those treated with psychotherapy only; and $51 008 for those treated with a combination of antidepressants and psychotherapy. As compared to no depression treatment, those who received antidepressants only, psychotherapy only, or a combination of antidepressants and psychotherapy had higher healthcare expenditures. However, second-year expenditures did not significantly differ among depression treatment categories. CONCLUSIONS: Among cancer survivors with newly diagnosed depression, depression treatment did not have a significant effect on expenditures in the long term.